Development of the Colorado posterior cortical questionnaire within an Alzheimer's disease study cohort. Issue 3 (16th March 2022) - Holden, Samantha K.; Pelak, Victoria S.; Sooy, Trevor; Heffernan, Kate S.; McConnell, Brice V.; Pressman, Peter S.; Bettcher, Brianne M.
ABSTRACT: Introduction: Non-amnestic presentations of neurodegenerative dementias, including posterior- and visual-predominant cognitive forms, are under-recognized. Specific screening measures for posterior cortical symptoms could allow for earlier, more accurate diagnosis and directed treatment. Methods: Based on clinical experience with posterior cortical atrophy evaluations, high-yield screening questions were collected and organized into a 15-item self-report questionnaire, titled the Colorado Posterior Cortical Questionnaire (CPC-Q). The CPC-Q was then piloted within a longitudinal cohort of cognitive aging, including 63 older adults, including healthy older adults (n = 33) and adults with either amnestic Alzheimer's disease (n = 21) or posterior cortical atrophy (PCA, n = 9). Results: The CPC-Q demonstrated acceptable psychometric properties (internal consistency, α = 0.89; mean item-total correlation = 0.62), correlated strongly with visuospatial measures on cognitive testing (p < 0.001), and could distinguish PCA from non-PCA groups (p < 0.001; AUC 0.95 (95% CI 0.88, 1.0)). Conclusions: The CPC-Q captured posterior cortical symptoms in older adults, using a gold standard of expert consensus PCA diagnosis. Future studies will validate the CPC-Q in a larger cohort, with recruitment of additional PCA participants, to evaluate its convergent and discriminant validity more thoroughly. As a short, self-report tool, the CPC-Q demonstrates potential to improve detection of non-amnestic neurodegenerative dementias in the clinical setting.